Tau as a therapeutic target in neurodegenerative disease - Himmelstein, Diana S. (2012)
Tau is a microtubule-associated protein thought to help modulate the stability of neuronal microtubules. In tauopathies, including Alzheimer’s disease and several frontotemporal dementias, tau is abnormally modified and misfolded resulting in its disassociation from microtubules and the generation of pathological lesions characteristic for each disease. A recent surge in the population of people with neurodegenerative tauopathies has highlighted the immense need for disease-modifying therapies for these conditions, and new attention has focused on tau as a potential target for intervention. In the current work we summarize evidence linking tau to disease pathogenesis and review recent therapeutic approaches aimed at ameliorating tau dysfunction. The primary therapeutic tactics considered include kinase inhibitors and phosphatase activators, immunotherapies, small molecule inhibitors of protein aggregation, and microtubule-stabilizing agents. Although the evidence for tau-based treatments is encouraging, additional work is undoubtedly needed to optimize each treatment strategy for the successful development of safe and effective therapeutics.